Synergistic recruitment of UbcH7 Ub and phosphorylated Ubl domain triggers parkin activation. (16th November 2018) - Condos, Tara EC; Dunkerley, Karen M; Freeman, E Aisha; Barber, Kathryn R; Aguirre, Jacob D; Chaugule, Viduth K; Xiao, Yiming; Konermann, Lars; Walden, Helen; Shaw, Gary S
Abstract: The E3 ligase parkin ubiquitinates outer mitochondrial membrane proteins during oxidative stress and is linked to early‐onset Parkinson's disease. Parkin is autoinhibited but is activated by the kinase PINK1 that phosphorylates ubiquitin leading to parkin recruitment, and stimulates phosphorylation of parkin's N‐terminal ubiquitin‐like (pUbl) domain. How these events alter the structure of parkin to allow recruitment of an E2 Ub conjugate and enhanced ubiquitination is an unresolved question. We present a model of an E2 Ub conjugate bound to the phospho‐ubiquitin‐loaded C‐terminus of parkin, derived from NMR chemical shift perturbation experiments. We show the UbcH7 Ub conjugate binds in the open state whereby conjugated ubiquitin binds to the RING1/IBR interface. Further, NMR and mass spectrometry experiments indicate the RING0/RING2 interface is re‐modelled, remote from the E2 binding site, and this alters the reactivity of the RING2(Rcat) catalytic cysteine, needed for ubiquitin transfer. Our experiments provide evidence that parkin phosphorylation and E2 Ub recruitment act synergistically to enhance a weak interaction of the pUbl domain with the RING0 domain and rearrange the location of the RING2(Rcat) domain to drive parkin activity. Synopsis: The multidomain E3 ubiquitin ligase parkin, which ubiquitinates outer mitochondrial membrane proteins in response to oxidative stress, otherwise resides in an auto‐inhibited state. Structural models incorporating new NMR and mass spectrometric data reveal how phosphorylation of its ubiquitin‐like (Ubl) domain and interaction with a phosphorylated ubiquitin allow the E3 ligase to recruit an E2 Ub conjugate needed for the ubiquitination process. The phosphorylated parkin Ubl domain samples a large conformational space that includes binding to the RING0 domain of parkin. A UbcH7‐Ub conjugate binds to parkin in an open configuration and causes re‐modeling of the C‐terminal catalytic region of parkin that facilitates pUbl interaction. UbcH7‐Ub binding to phosphorylated parkin in complex with phospho‐ubiquitin causes large conformational changes in parkin. Both UbcH7‐Ub and pUbl recruitment are needed to fully optimize parkin ubiquitination activity. Abstract : Modeling based on NMR and mass spectrometry data reveals how PINK1‐mediated phosphorylation allows E2 enzyme binding and subsequent remodeling of the autoinhibited multi‐domain E3 parkin into an active E3 ligase.